Embedding corporate responsibility and sustainability: Marks and Spencer - Grayson, David (Emerald Group Publishing Limited, 2011)
Purpose – The British retailer Marks & Spencer aspires to be the world's most sustainable major global retailer by 2015. This paper seeks to examine how the company is embedding sustainability. Design/methodology/approach – The paper is written as part of an ongoing investigation into how businesses do this. It is based on direct dialogue with corporate sustainability specialists inside and outside the company; participation in company stakeholders' briefings held regularly since the launch of Marks & Spencer's Plan A for sustainability in January 2007; and analysis by the company's own corporate sustainability specialists about how they are embedding. Findings – This case demonstrates that, in order to speed their journey, Marks & Spencer have aligned sustainability with core strategy. Top leadership is driving the strategy, which is overseen by the board. M&S have made a very public commitment: Plan A with measurable targets, timescales and accountabilities. The strategy is being integrated into every business function and strategic business unit; and involves suppliers, employees and increasingly customers. To enable implementation, the company is developing its knowledge-management and training; engaging with wider stakeholders including investors; building partnerships and collaborations; and has evolved its specialist sustainability team into an internal change-management consultancy and coach/catalyst for continuous improvement. Originality/value – The value of the case study is that it provides an analysis of how one company, which has been active in progressing corporate sustainability, has evolved its approach in recen